Preliminary risk assessment of PFOS in former production sites: A case study in Hubei, China - Yiming Jiang; Ning Fang; Qiang Chen; Tao Long; Roland Weber; Jun Huang (Emerging Contaminants)
Sound management of contaminated sites, particularly former manufacturing sites with potential heavy contamination, is crucial for the Parties to implement the Stockholm Convention on Persistent Organic Pollutants (POPs). Unfortunately, numerous former manufacturing sites in developing countries have not been well investigated, especially for those associated with newly listed POPs such as perfluorooctane sulfonate (PFOS). Following 3M's voluntary phase-out plan in 2002, China emerged as the primary producer of PFOS and ceased production in 2021. However, little information is available about the contamination levels at these former PFOS production sites. This study focused on five specific sites located in Hubei, China. Soil and groundwater samples, both on-site and off-site, were collected for PFOS analysis. Concentrations ranging from 392 μg/kg to 7.78 × 105 μg/kg in on-site soil, 5.05 μg/kg to 83.2 μg/kg in off-site soil, and 84.1 μg/L to 1.74 × 103 μg/L in groundwater samples were found, respectively. By employing current national standards in China (i.e. GB 36600-2018 and HJ 25.3–2019), PFOS screening and management levels were established for risk assessment purposes. Preliminary risk assessments showed that 34 % and 100 % of the sampling points would pose unacceptable risks when evaluated using two distinct PFOS characteristic databases. The results highlight the significant health risk caused by PFOS at former production sites as well as the urgent need for regulatory interventions.